2013
DOI: 10.1007/s00424-013-1372-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of mechanosensitive AT1B receptors in myogenic vasoconstriction

Abstract: Myogenic vasoconstriction is an inherent property of vascular smooth muscle cells (VSMCs) of resistance arteries harboring ill-defined mechanosensing and mechanotransducing elements. G protein-coupled receptors (GPCRs) are discussed as mechanosensors in VSMCs. In this study, we sought to identify and characterize the role and impact of GPCRs on myogenic vasoconstriction. Thus, we analyzed mRNA expression levels of GPCRs in resistance versus preceding conduit arteries revealing a significant enrichment of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 35 publications
4
48
0
Order By: Relevance
“…13,15,21 Moreover, there is evidence that overexpression of AT 1 Rs causes proteinuria, 22 and AT 1 R antagonists and angiotensin-converting enzyme inhibitors are protective for podocytes and can improve proteinuria. 23,24 Therefore, we analyzed the role of G q/11 PCRs as potential mechanosensors in podocytes.…”
Section: G Q/11 -Pcrs Are Not Mechanosensors In Podocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…13,15,21 Moreover, there is evidence that overexpression of AT 1 Rs causes proteinuria, 22 and AT 1 R antagonists and angiotensin-converting enzyme inhibitors are protective for podocytes and can improve proteinuria. 23,24 Therefore, we analyzed the role of G q/11 PCRs as potential mechanosensors in podocytes.…”
Section: G Q/11 -Pcrs Are Not Mechanosensors In Podocytesmentioning
confidence: 99%
“…10 Because the podocin homolog MEC-2 is part of a mechanosensitive multiprotein ion channel complex in Caenorhabditis elegans, it was suggested that TRPC6 in complex with other slit-membrane proteins (including podocin) could form a mechanosensitive ion channel complex. 2 Of note, in our previous studies, G q/11 -proteincoupled receptors (G q/11 PCRs) and not TRPC6 channels shaped up as mechanosensors in vascular smooth muscle cells 13,15 contributing to myogenic vasoconstriction. There is still growing evidence for an inherent mechanosensitivity of G-protein-coupled receptors (GPCRs) in other tissues and organs (summarized by Storch et al 16 ).…”
mentioning
confidence: 93%
“…Investigating both murine AT 1 R isoforms, we recently found that mechanosensitive AT 1B but not AT 1A receptors are key elements for mechanosensation in VSMC mediating myogenic tone. 5 However, myogenic tone was not completely lost in AT 1B gene-deficient arteries or after blockade of AT 1 Rs with candesartan or losartan, suggesting that other signaling pathways might participate in myogenic tone. The aim of this study was to analyze the total effect of AT 1A and AT 1B receptors on myogenic tone by investigating AT 1A/1B double gene-deficient (AT 1A/1B −/− ) mice and to discover novel candidate mechanosensors in the vasculature.…”
mentioning
confidence: 99%
“…Recently, angiotensin II AT 1 receptors (AT 1 Rs) emerged as mechanosensors in VSMCs mediating myogenic tone and in cardiac myocytes inducing cardiac hypertrophy independent of agonist. [5][6][7][8][9] Numerous other G-protein-coupled receptors, such as the bradykinin B 2 , the endothelin ET A , the parathyroid hormone type 1, the histamine H 1 , the muscarinic M 5 , and the formyl peptide 1, are discussed as mechanosensors. 10 For some of these receptors, physiological roles emerged, for example, as sensors of fluid shear stress in endothelial cells, for retraction of pseudopods in neutrophils or for bone growth.…”
mentioning
confidence: 99%
“…6, 8, 25, 26 The current experiments were aimed at extending this to investigate how mechanosensitive GPCR-mediated myogenic responsiveness is regulated. Specifically, using isolated arteriolar VSMCs and cannulated arterioles, the present studies focused on RGS5-mediated regulation of the AT 1 R during mechanical (ligand-independent) or Ang II (ligand-dependent) activation.…”
Section: Discussionmentioning
confidence: 99%